On the Cost-Effective Design of Agglomeration Bonus Schemes for the Conservation of Multiple Competing Species - Drechsler, Martin (Frontiers in Ecology and Evolution, 2021)
An important mechanism of species co-existence in spatially structured landscapes is the competition-colonisation trade-off which states that co-existence of competing species is possible if ceteris paribus the better competitor is the worse coloniser. The effectiveness of this trade-off for the facilitation of co-existence, however, is likely to depend on the spatial arrangement of the habitat, because too strong agglomeration of the habitat may overly benefit the strong competitor (being the poor disperser), implying extinction of the inferiour competitor, while too much dispersion of the habitat may drive the superiour competitor (being the inferiour coloniser) to extinction. In working landscapes, biodiversity conservation is often induced through conservation payments that offset the forgone profits incurred by the conservation measure. To control the spatial arrangement of conservation measures and habitats in a conservation payment scheme, the agglomeration bonus has been proposed to provides financial incentives for allocating conservation measures in the vicinity of other sites with conservation measures. This paper presents a general spatially explicit ecological-economic simulation model to explore the ability of the agglomeration bonus to cost-effectively conserve multiple competing species that differ by their competition strengths, their colonisation rates and their dispersal ranges. The interacting effects of the agglomeration bonus and different species traits and their trade-offs on the species richness in the model landscape are analysed. Recommendations for the biodiversity-maximising design of agglomeration bonus schemes are derived.